Using simulation to understand the structure and properties of hydrated amorphous calcium carbonate. Issue 1 (26th November 2015) - Innocenti Malini, Riccardo; Bushuev, Yuriy G.; Hall, Shaun A.; Freeman, Colin L.; Rodger, P. Mark; Harding, John H.
Abstract : The protocols used give a range of behaviours comparable to previous experiments and an insight into the structure of ACC. Abstract : We report results from studies using four different protocols to prepare hydrated amorphous calcium carbonate, ranging from random initial structures to melting hydrated mineral structures. All protocols give good agreement with experimental X-ray structure factors. However, the thermodynamic properties, ion coordination environments, and distribution of water for the structures produced by the protocols show statistically significant variation depending on the protocols used. We discuss the diffusivity of water through the various structures and its relation to experiments. We show that one protocol (based on melting ikaite) gives a structure where the water is mobile, due to the presence of porosity in the amorphous structure. We conclude that our models of hydrated amorphous calcium carbonate do give a range of behaviour that resembles that observed experimentally, although the variation is less marked in the simulations than in experiments.